2019
DOI: 10.3390/ijms20051092
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone Selectively Kills Hypoxic Renal Cancer Cells by Suppressing HIF-1α-Mediated Glycolysis

Abstract: Several reports have shown that thymoquinone (TQ) effectively attenuates angiogenesis in cancer cells, resulting in suppression of tumor growth. However, it is not yet clear whether TQ reduces hypoxia-inducible factor-1α (HIF-1α) expression in hypoxic cancer cells. Here, we found that TQ was a novel HIF-1α inhibitor through hypoxia response element (HRE)-luciferase assay-based large screening by using 502 natural compounds containing chemical library. TQ reduced HIF-1α protein levels in renal cancer cells; how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 38 publications
1
34
0
Order By: Relevance
“…Following phosphorylation by GSK3β, HIF-1α ubiquitination via FBXW7 is increased, which promotes proteolysis of HIF-1α and inhibits tumor growth [136]. Anticancer drug glyceollins and thymoquinone can inhibit tumor growth by elevating ubiquitination and degradation of HIF-1α [137,138]. E3 ligase FBX11 can reduce the mRNA stability rather than protein stability of HIF-1α [139].…”
Section: Ubiquitination and Transcription Factorsmentioning
confidence: 99%
“…Following phosphorylation by GSK3β, HIF-1α ubiquitination via FBXW7 is increased, which promotes proteolysis of HIF-1α and inhibits tumor growth [136]. Anticancer drug glyceollins and thymoquinone can inhibit tumor growth by elevating ubiquitination and degradation of HIF-1α [137,138]. E3 ligase FBX11 can reduce the mRNA stability rather than protein stability of HIF-1α [139].…”
Section: Ubiquitination and Transcription Factorsmentioning
confidence: 99%
“…Those genes are widely involved in energy metabolism, angiogenesis, apoptosis, and other genes whose protein products increase oxygen delivery or facilitate metabolic adaptation to hypoxia. [41][42][43] Hence, we believed that AGR2 could affect the apoptotic proteins expression via modulating HIF-1α.…”
mentioning
confidence: 99%
“…As the main producer of ROS in hypoxic cells, mitochondria determine the fate of cells under hypoxic conditions [21]. Our previous studies focused on the metabolic reprogramming in ocular diseases and found that the promotes ATP generation by enhancing anaerobic glycolysis [25][26][27]. For instance, HIF-1α induces cellular ROS production, inhibits mitochondrial respiration and electron transfer chain activity, while inducing glucose transporters, glycolytic enzymes, and apoptotic protein BNIP3 gene transcription, which increases the flow from glucose to lactic acid [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…The role of HIF-1α in metabolic pathways can further help elucidate the effects of PSF on the bioenergetics pattern in HRMECs. Previous studies have reported that enhanced and stabilized HIF-1α regulates mitochondrial dynamics in hypoxia-induced pulmonary vascular remodeling and promotes ATP generation by enhancing anaerobic glycolysis [ 25 – 27 ]. For instance, HIF-1α induces cellular ROS production, inhibits mitochondrial respiration and electron transfer chain activity, while inducing glucose transporters, glycolytic enzymes, and apoptotic protein BNIP3 gene transcription, which increases the flow from glucose to lactic acid [ 28 30 ].…”
Section: Discussionmentioning
confidence: 99%